Well Begun, but Aiming Higher : A Review of Vietnam’s Education Trends in the past 20 Years and Emerging Challenges - Dang, Hai-Anh H.; Glewwe, Paul W. (Taylor and Francis, 2018)
Given its modest position as a lower-middle-income country, Vietnam stands out from the rest of the world with its remarkable performance on standardized test scores, school enrollment, and completed years of schooling. We provide an overview of the factors behind this exemplary performance both from an institutional viewpoint and by analyzing several different data sources, some of which have rarely been used. Some of the highlights are universal primary school enrollment, higher girls’ net enrollment rates, and the role of within-commune individual factors. We further discuss a host of challenges for the country – most of which have received insufficient attention to date.